The Development of a Virtual Laboratory on Qualitative Chemical Practicum Analysis - Widarti, Hayuni Retno; Hakim, Moh Ilmanul; Rokhim, Deni Ainur (Jurnal Ilmiah Peuradeun, 2022)
In practical activities, it is necessary to have media that can provide multi-representation explanations, namely macroscopic, microscopic and submicroscopic, especially in qualitative analytical chemistry for group I and II cations. It takes an innovation of practicum learning media that can explain multiple representations to prepare students for practical activities well. An alternative solution is to use learning media as a virtual laboratory. The objectives of this research and development were to develop a virtual laboratory in qualitative chemical analysis practicum for group I and II cations based on multiple representations with internet integration and describe the feasibility of a virtual laboratory in the practicum of qualitative chemical analysis of group I and II cations based on multiple representations with internet integrated. This research and development used the R & D (research and development) method with a 4D (four-D) development model. The results showed that media expert validation was 87.8% (very valid), and material validation was 82.7% (very valid). The readability test results obtained percentage values ​​of 91.1% and 92.3% (Very Valid). The virtual laboratory explained multiple representations that can help students in practical activities well.